Book Review: Marcus Callies and Sandra Götz (eds.). (2015). Learner corpora in language testing and assessment (Studies in Corpus Linguistics 70) Amsterdam/ Philadelphia: John Benjamins, pp 220 - Jesús García Laborda (Revista de Lenguas para Fines Específicos, 2016)
Book Review: Marcus Callies and Sandra Götz (eds.). (2015). Learner corpora in language testing and assessment (Studies in Corpus Linguistics 70) Amsterdam/ Philadelphia: John Benjamins, pp 220